Chronic treatment with a mild dose of NaF promotes dyslipidemia in rats - Chiba, Fernando Y. [UNESP]; Garbin, Cléa A.S. [UNESP]; Mattera, Maria S.L.C. [UNESP]; Mota, Max S.O. [UNESP]; Pereira, Renato F. [UNESP]; Sumida, Doris H. [UNESP] (My University, 2015)
Excessive fluoride ion (F) intake promotes systemic metabolic alterations, such as a decrease in insulin secretion, hyperglycemia, and insulin resistance, similar to those observed in diabetes. Cardiovascular disease is responsible for a large degree of morbidity and mortality in individuals with diabetes, and dyslipidemia is considered to be one of the most important risk factors for the development of cardiovascular disease. This study aimed to evaluate the chronic effect of NaF on insulin signal transduction in liver and in muscle, and to determine the plasma concentrations of triglycerides (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and very low-density lipoprotein cholesterol (VLDL-C). Seven-week-old castrated male Wistar rats were randomly distributed into a control group, which received 76.4 mg/ L NaCl in their drinking water, and a fluoride group, which received 54.9 mg/L NaF in their drinking water and F in their food pellets (estimated total F intake: 4.0 mg/kg body weight (bw)/day). After 42 days, the insulin receptor substrate-1 (IRS-1) serine phosphorylation status in the liver and muscle tissues and plasma concentrations of triglycerides, total cholesterol, HDL-C, LDL-C, VLDL-C and F were evaluated. The chronic treatment with F promoted an increase in the plasma concentrations of TG, TC, VLDL-C and F but no alteration in the plasma concentrations of HDL-C and LDLC or in the IRS-1 serine phosphorylation status in liver or muscle tissue. These results demonstrate that chronic treatment with NaF (4.0 mg/kg bw/day) promotes dyslipidemia in castrated rats but does not interfere with the IRS-1 serine phosphorylation status, one of the inhibitory pathways of the insulin signal in muscle and liver tissues.
Keywords: Cholesterol; Diabetes mellitus; Dyslipidemia; Insulin receptor substrate-1; Insulin resistance; IRS-1 serine phosphorylation status; Triglycerides